Overview Of The Main Viral And Protozoan Infections In Humans - Padkowska, Aleksandra; Pieniążek, Jakub Maciej; Arciszewska, Klaudia; Dobosz, Mateusz; Buczkowski, Jakub; Mataczyńska, Anna; Paprocki, Michał (Quality in Sport, 2024)
Both viral and protozoan infections pose a serious health risk worldwide, e.g. due to their varied intensity of symptoms - from mild to even lethal. This overview focuses on some of the most important infections caused by these pathogens that still remain a huge concern in some parts of the world. Viral and protozoan infections contribute significantly not only to morbidity, but also mortality, for the most part in regions with limited access to healthcare with low vaccination coverage. Diseases on their own sometimes are mild or even asymptomatic, but the complications or the infections during pregnancy are the reasons why those diseases still remain a huge concern because they may result in serious conditions. Information searches were carried out in online databases, scientific and educational editions, including PubMed, Elsevier, Research Gate, Springer, CDC, WHO. Understanding the biology, transmission routes and severity of those infections as well as pathogenesis of agents that cause them are essential for effective treatment and decline in severe cases and complications.